Thrombolysis and bridging therapy in patients with acute ischaemic stroke and Covid‐19. (15th October 2020) - Cappellari, M.; Zini, A.; Sangalli, D.; Cavallini, A.; Reggiani, M.; Sepe, F. N.; Rifino, N.; Giussani, G.; Guidetti, D.; Zedde, M.; Marcheselli, S.; Longoni, M.; et al.
Abstract : Background and purpose: Comorbidity of acute ischaemic stroke with Covid‐19 is a challenging condition, potentially influencing the decision of whether to administer intravenous thrombolysis (IVT). We aimed to assess the 1‐month outcome in ischaemic stroke patients with Covid‐19 infection who received IVT alone or before thrombectomy (bridging therapy). Methods: As a collaboration initiative promoted by the Italian Stroke Organization, all Italian stroke units ( n  = 190) were contacted and invited to participate in data collection on stroke patients with Covid‐19 who received IVT. Results: Seventy‐five invited centers agreed to participate. Thirty patients received IVT alone and 17 received bridging therapy between 21 February 2020 and 30 April 2020 in 20 centers ( n  = 18, Northern Italy; n  = 2, Central Italy). At 1 month, 14 (30.4%) patients died and 20 (62.5%) survivors had a modified Rankin Scale (mRS) score of 3 to 5. At 24 to 36 hours, asymptomatic intracerebral hemorrhage (ICH) was reported in eight (17.4%) patients and symptomatic ICH (sICH) in two (4.3%) patients. Causes of death were severe ischaemic stroke ( n  = 8), a new ischaemic stroke ( n  = 2), acute respiratory failure ( n  = 1), acute renal failure ( n  = 1), acute myocardial infarction ( n  = 1), and endocarditis ( n  = 1). In survivors with a 1‐month mRS score of 3 to 5, baseline glucose level was higher, whereas endovascular procedure time in cases of bridging therapy was longer. Baseline National Institutes of Health Stroke Scale glucose and creatinine levels were higher in patients who died. Conclusions: Intravenous thrombolysis for patients with stroke and Covid‐19 was not a rare event in the most affected areas by pandemic, and rates of 1‐month unfavorable outcomes were high compared to previous data from the pre–Covid‐19 literature. However, risk of sICH was not increased. Abstract : Seventy‐five centers agreed to participate in the study. Forty‐seven stroke patients with Covid‐19 were treated with thrombolysis alone ( n = 30) or bridging therapy ( n = 17) in 20 centers ( n = 18, Northern Italy; n = 2, Central Italy). During the study period, 283 stroke patients were treated with thrombolysis alone ( n = 266, Northern Italy; n = 17, Central Italy) and 167 stroke patients with bridging therapy ( n = 156, Northern Italy; n = 11, Central Italy) in the 20 enrolled centers. Rates of 1‐month unfavorable outcomes (death: 30.4%; mRs score 3–5: 62.5%) were high compared to previous data from the pre–Covid‐19 literature. However, risk of sICH (4.3%) was not increased.